Doing Away with Skepticism about Harm - Folland, Anna (Ethical theory and moral practice, 2025)
The concept of harm plays a central role in many philosophical discussions. There are numerous ethical theories, claims, and arguments that appeal to the concept of harm. However, some philosophers think that the concept of harm is not fit to play this role in philosophical theorizing. Bradley (2012) argues that the concept is problematic to such an extent that we should do away with it. Bradley is not the only philosopher who doubts this concept’s usefulness, although others make more modest and suggestive skeptical claims. In this paper, I examine several claims in support of skepticism, which are explicitly embraced or hinted to in the literature. Some examples are the claims that the harm concept is defective and that harm is morally insignificant. Neither those claims nor others, I argue, yield a good case for skepticism about harm.